Study of outcomes of suprapatellar approach for tibia intramedullary nailing in patients coming to rural medical college, Loni - Patel, Nevish H.; Herode, Prafulla G.; Patel, Het R. (International Journal of Research in Orthopaedics, 2022)
Background: Tibia shaft fractures are most common lower limb long bone fractures. In approximately 80% of patients, tibia fracture occurs in diaphysis region. The procedure of intramedullary interlocking nailing is done by positioning the injured extremity at minimum of 90 degree of flexion in the knee joint to achieve optimal exposure of correct entry point. The tension of quadriceps tendon causes a typical apex anterior angulation of proximal fragment. Supra patellar nailing is done with knee in semi extended position, reducing the anterior angulation. The aim of this study is to study outcomes of supra patellar access of intramedullary nailing for tibia fractures. Methods: It is a descriptive longitudinal study which was carried out from October 2019 to September 2021 in Dr. Balasaheb Vikhe Patil rural medical college, Loni, Ahmednagar. In this study 60 case of closed shaft tibia fractures were treated by supra-patellar nailing technique. Results: In our study we selected, 60 patients with tibia fracture admitting in our institute. All patients underwent operative procedure in the form of intramedullary interlocking tibia nail which was done with suprapatellar approach. Out of all the 60 patients treated with suprapatellar approach, excellent results with good range of movements with excellent lower extremity functional scale score. Conclusions: Supra-patellar approach was found to provide excellent outcome for proximal 1/3rd of tibia fracture.